Acute gastroenteritis due to Arcobacter butzleri: an emerging pathogen - Cristina García-Salguero; Carlos González-Corralejo; Jose Marroyo Laso; Alberto Delgado-Iribarren García-Campero (Gut Pathogens)
Abstract Arcobacter butzleri is a foodborne pathogen that has been positioned as an emerging cause of bacterial enteritis. It can affect any type of person although vulnerable people are more susceptible. In addition, resistance to several antibiotics has been described, which is a problem for antimicrobial empirical treatment and this makes it a threat to public health. Seven isolates of this pathogen were collected during 2024. Susceptibility studies were performed on first-line antibiotics for the treatment of gastroenteritis in our epidemiological environment. Resistance rates higher than 25% were observed for all antimicrobials tested, except erythromycin. Based on these data, it would be necessary to carry out a study of antimicrobial resistance profile of this microorganism for their treatment and control.